Colonização de terras na área indígena de Serrinha (1950-2003): um estudo de caso - Bonavigo, Mateus Manfrin (2020)
This Course Conclusion Work is based on the historical events of occupation and agrarian territorialization of the Serrinha Indigenous Reserve in the North of Rio Grande do Sul (RS), with a comprehensive area in the municipalities of Ronda Alta, Três Palmeiras, Engenho Velho and Constantina, between the 1950s, where settlers entered the territory referring to part of the 1st and 2nd Sections Alto Recreio, in the region of the municipality of Ronda Alta, up to the year 2003, where the settlers were expelled from the territory by the process of indigenous resumption of that area. The work is based on historiographical analyzes and private documentation, referring to the process of legalization by the State, of colonization in that territory in the 1960. We seek to understand through colonization, who has the right to occupy the territory of Serrinha: Indians or settlers or both? And the responsibility of the State to resolve the agrarian conflicts between the two groups, so that both have benefited, as not it happened.